Efeito da rACLF, uma metalopeptidase recombinante da peçonha de Agkistrodon contortrix laticinctus, na viabilidade celular, expressão de citocinas e degradação de proteínas da matriz extracelular - Moraes, Caroline Krieger de (2006)
ACLF is a fibrinolytic non-hemorrhagic metallopeptidase from the venom of the snake Agkistrodon contortrix laticinctus. rACLF is synthesized as a zymogen (pro- ACLF) with 412 aminoacids, while the active form of enzyme has 222 aminoacids. The ORF (open reading frame) that codes for the peptidase was isolated (from a cDNA venom gland library of A. contortrix. lacticinctus ) and characterized. This work shows the effects of rACLF on endothelial cells (HUVECs), tumor cells (HeLa, MDA-MB-231 and MCF-7) and non-tumor cell (fibroblast) as well its proteolytic activity on extracellular matrix proteins. Our results showed that rACLF inhibited the apoptosis induced by serum deprivation in HUVECs, but had no effect on cell proliferation. rACLF had direct effect on HUVECs, since it was observed an increased amount of IL-8 in the cell supernatants, in addition to the expression induction of molecules related to adhesion and inflammation processes. rACLF and rACLH were not cytotoxic to human fibroblasts. On the other hand, both proteins caused decrease of cell viability, changes in morphology, and detachment of HeLa cells. On human fibroblasts, rACLF modulated the expression of chemokines CXC, IL-8 and GRO, and chemokine CC, MCP1. The supernatant of human fibroblasts and HeLa cells were analyzed for MMP-2 (gelatinase-A) secretion. No difference was observed after 48 h incubation with rACLF and controls. rACLF presented hydrolytic activity on extracellular matrix proteins, such as laminin, fibronectin, collagen IV, and thrombospondin. Furthermore, hydrolytic activity on insulin β chain peptide was tested and compared to rACLH activity. rACLF was shown to be more efficient than rACLH on this substrate. In conclusion, the results of this study increased the knowledge on the protein effects on different cell lines and open up perspectives for new studies concerning signaling and regulation mechanisms affected by this protein activity.